2018
DOI: 10.1186/s40608-018-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Markers with self-reported osteoarthritis among middle-aged BMI-defined non-obese individuals: a cross-sectional study

Abstract: BackgroundOsteoarthritis (OA) is a chronic degenerative joint disease. While it is well-established that obesity affects OA through increased axial loading on the joint cartilage, the indirect effect of obesity through metabolic processes among the body mass index (BMI)-defined non-obese population, i.e., BMI < 30 kg/m2, is less known. Our goal was to evaluate the association of metabolic markers including body fat percentage (BF%), waist circumference, maximum weight gain during adulthood and serum creatinine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Then, full articles were extracted for further assessment after reviewing the titles and abstracts. Eventually, 19 studies (10 cross‐sectional, 5 case‐control and 4 cohort studies) were included in the present systematic review and meta‐analysis. The study screening process is shown in Figure , and the study characteristics and NOS score of the 19 included articles are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, full articles were extracted for further assessment after reviewing the titles and abstracts. Eventually, 19 studies (10 cross‐sectional, 5 case‐control and 4 cohort studies) were included in the present systematic review and meta‐analysis. The study screening process is shown in Figure , and the study characteristics and NOS score of the 19 included articles are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported the OR of knee OA for each standard deviation or 5‐unit increase in fat mass percentage. Three studies reported the OR comparing the highest category to lowest category in fat mass percentage. The pooled results showed that fat mass percentage was positively associated with knee OA, with statistical significance (OR = 1.72, 95% CI: 1.26‐2.35 for per SD or five units; OR = 1.97, 95% CI: 1.27‐3.04 for the highest category to lowest category) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…28 The pathogenesis of osteoarthritis is related to obesity through excessive joint loading, altered biomechanics, inflammation related to adipose tissue, and potential hormonal dysregulation. 16,29,30 Thus, osteoarthritis may cause pain in weight-bearing and non-weight-bearing joints. 31,32 Obesity duration may also increase the risk of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no disease-modifying OA drugs (DMOADs), and the primary therapies include exercise and nonsteroidal anti-inflammatory drugs until total joint replacement at the end-stage of the disease. Clinical risk factors for the development of OA include increasing age, female sex, obesity, repetitive joint overloading, previous joint injury, lower limb deformity, smoking history, and family history of OA [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. This wide array of contributing factors for the initiation and progression of OA supports the notion that OA is not simply one disease, but rather a family of conditions that have similar endpoints that involve a multitude of pathways that lead to joint failure.…”
Section: Introductionmentioning
confidence: 82%
“…As the severity of symptomatic arthritic diseases and pain can fluctuate over time [39], development of specific therapeutic strategies that can sense and respond to varying degrees of endogenous inflammatory mediators in OA may mitigate unwanted adverse effects. In recent studies, CRISPR-Cas9 gene editing was used to develop an autoregulated anti-cytokine stem cell system in mouse induced pluripotent stem cells (iPSCs), which provides the opportunity to theoretically differentiate them into a variety of cell types [11,12]. These cells were designed to transcribe the soluble receptor for TNF-a (sTNFR1), interleukin-1 receptor antagonist (IL1Ra), or luciferase (control) in a feedback-controlled manner driven by the endogenous macrophage chemoattractant protein-1 (Ccl2) promoter (Fig.…”
Section: Applications Of Genome-engineering Technologies To Osteoarthritis Treatmentsmentioning
confidence: 99%